ENHANCING LANGUAGE PROFICIENCY: A COMPREHENSIVE APPROACH TO TEACHING RUSSIAN GRAMMAR (Journal of Science-Innovative Research in Uzbekistan, 2024)
This scientific article explores the intricacies of teaching Russian grammar and proposes a comprehensive approach to enhance language proficiency. Russian, with its rich linguistic heritage, presents unique challenges for learners, particularly in mastering its complex grammatical structures. The article discusses effective pedagogical strategies, modern technology integration, and the importance of cultural context in facilitating a holistic understanding of Russian grammar. The proposed approach aims to create an engaging and immersive learning environment, fostering not only grammatical accuracy but also cultural competence among learners